2015
DOI: 10.1016/j.anndiagpath.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in pleomorphic lobular carcinoma: a case-control study with comparison to classic invasive lobular carcinoma

Abstract: Aim Pleomorphic lobular carcinoma (PLC) is a variant of invasive lobular carcinoma (ILC) that is described in the literature as an aggressive tumor with poor prognosis. Multiple studies have shown a decrease in overall survival when compared to classic ILC (cILC). In the current study, we sought to compare the clinicopathologic parameters of PLC to cILC. Materials and methods All cases with a diagnosis of ILC, Nottingham grade II-III between 1990 and 2010 were retrieved from the pathology files in the anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
4
23
3
Order By: Relevance
“…In our cases, the patients in the PLC group were older and had a higher incidence of axillary lymph node metastasis compared to non‐PLC patients, and both were factors associated with a worse prognosis. However, we were not able to identify a significant difference in the clinical follow‐up data between the two groups, consistent with reports by Jacobs and Narendra . Based on our findings, it is tempting to assume that PLC may not be an aggressive subtype of breast cancer, as has been reported previously.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In our cases, the patients in the PLC group were older and had a higher incidence of axillary lymph node metastasis compared to non‐PLC patients, and both were factors associated with a worse prognosis. However, we were not able to identify a significant difference in the clinical follow‐up data between the two groups, consistent with reports by Jacobs and Narendra . Based on our findings, it is tempting to assume that PLC may not be an aggressive subtype of breast cancer, as has been reported previously.…”
Section: Discussionsupporting
confidence: 86%
“…Narendra et al . compared the clinical outcomes of 52 PLC and 103 classic ILC patients and found that disease‐free survival and overall survival were similar between the two groups, both of which were dependent on their disease stage, tumour size and lymph node status . Rakha et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations